CSEP: Circular Shifting Encryption Protocols for Location Privacy Protection - Chen Di; Zhao Binglin; Li Hao; Zhou Shilei (International Journal of Networked and Distributed Computing (IJNDC), 2017)
Location Based Service (LBS) is gaining popularity. As one fundamental LBS service, range search returns all Point of Interests (POIs) within a user-specified range. However, people leave their location privacy at risks when using range search. How to provide a high-quality range search service while protecting users’ location privacy is a challenging problem. Most existing approaches use space-filling curves and cloaked region method to provide privacy-preservation location services, but these methods cannot return the accurate results. In this paper, we propose a set of Circular Shifting Encryption Protocols (CSEP) based on homomorphism and circular shift for location privacy protection of range search. CSEP leverages homomorphism encryption to encrypt users’ locations, and LBS servers compute distances on cyphertext. In this way, LBS server can return POIs within the specified range, while learning nothing about the user’s real location. To accommodate the different query range and the private protection degree of users, we propose a circular shifting encryption method to reduce the redundancy and increase the degree of privacy protection. We implement a prototype of CSEP, and evaluate it with real POI set of a large-scale production LBS. Experimental results show that CSEP can provide reliable privacy protection and accurate range search, with reasonable compute overhead and communication overhead.